Heidegger's contribution to the understanding of work-based studies - Gibbs, Paul.; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2011)
This book seeks to develop the philosophy of Heidegger notion and reflects the growing importance of work based studies which is becoming of special interest to higher education institutions and commercial organisations. The author acknowledges the dominance of the economic discourse of higher education, but in this book he tries to argue that Heidegger offers a phenomenological approach to understanding the diversity to higher education that work based learning can bring. The book offers a structured argument for a phenomenological understanding of both the educational institution and the commercial environment to be considered as workplaces.
Introduction Background PART I. CONTEXT Chapter 1 Work-Based Learning as a Field of Study WBL: Roots in the Ancients Understanding Work-Based Learning Developing a Notion of the Field for Work-Based Learning Understanding Chapter 2 Learning as Knowledge of Being-in-the-World Learning as Being-in-the-World Capability, Potential and Actualization The Unconcealment of Being Through Learning The Concealment of Representational Thinking Existential Reflection Summary Chapter 3 Dwelling at Work Phronesis Technical Skill or the Embracing of a Craft?Turning to Heidegger The Tension Between Workplace Identity and Dispositions of Democracy What is the Evidence? Chapter 4 What is work? A Heideggerian Insight into Work as a Site for Learning Being and Work A Heideggerian Phenomenology of Workplace and Worker The Worker What Does Heidegger Offer the Researcher Investigating the Workplace? Summary Chapter 5 Heidegger; Time, Work and the Challenges for University Lead Work-Based Learning Heidegger and his Phenomena of Time Heidegger and his Phenomena of Historicity The Worker and the Labourer in the Age of Technology; Heidegger?s use of Jünger?s Works Questioning Temporality and Seeking an Originary Future: The Role of Higher Education Aspects of Work-Based Studies from a Heideggerian Perspective Part II?ISSUES IN WORK-BASED STUDIES Chapter 6 Quality in Work-Based Studies: Not Lost, Merely Undiscovered Quality and Work-Based Learning Quality in our Everydayness from a Heideggerian Perspective Quality Undisclosed A Conscience? The desire of disappearance Chapter 7 Assessment and Recognition of Work-Based Learning The Temporality of the Known; A Fore-Structure and Foreclosure of Assessment Tacit Knowledge Evidence Disclosing Educational Possibilities, not Assessing Explicitness of Learning Phenomenological Interpretations Chapter 8 Learning Agreement Entitlements and Evidence in Work-Based Learning Learning Agreements and Learning Contracts: What do they Promise? Entitlements Distribution and Exploitation The University as Accomplice Sources of Exploitation Built into the Negotiation of a WBS Learning Contract Chapter 9 A Heideggerian Phenomenology Approach to Higher Education as Workplace: A Consideration of Academic Professionalism Part 1: A Heideggerian Phenomenology of the World of Work Understanding the Meaning of the Workplace The Equipmental Nature of the Workplace Defining the Activities of the Workplace Part 2: Towards a Phenomenology of the Professional Academic Worker in Higher Education Where to, Next? Chapter 10 Adopting Consumer Time: Potential Issues for Higher Level Work-Based Learning Consumerism and the Changing Notion of Time Higher Level Work-Based Learning Heidegger Once Again Summary Chapter 11 The Concept of Boredom: Its Impact on Work-Based Learning Heidegger and the Experience of Boredom Three Explorations: Bore-by, bored-with, and profound boredom Bore-by Bored-with Profound boredom Summary Chapter 12 Practical Wisdom and the Workplace Researcher The Skills of Workplace Researchers Practical Enquiry The Purpose of the Action The Means to be Able to Act The feasibility of the act Determinate timing Respect for others Summary Chapter 13 The Recession and the World of Work-Based Studies Learning Capability The Workplace as a Learning Environment A Generalized Anxiety References Index.
Electronic reproduction.
Keywords: Heidegger, Martin -- 1889-1976.; Career education; Education, Higher; Phenomenology; Electronic books